A novel strategy to maintain the long-term viscosity stability of konjac glucomannan hydrosol by using zinc ion. (November 2020) - Hu, Ling; Wang, Shishuai; Shang, Longchen; Teng, Yongxin; Li, Jing; Li, Bin
Abstract: The viscosity of konjac glucomannan (KGM) hydrosol dropped sharply after a period of approximately 12 h. This is a well-known problem which producers are trying to solve. Several salts were added to KGM hydrosols to attempt to improve the long-term viscosity stability of KGM hydrosol. Compared with native KGM hydrosol and KGM hydrosol with Ca 2+ and Mg 2+, the initial apparent viscosity of KGM hydrosol with Zn 2+, in the form of zinc chloride was higher, and the long-term viscosity stability was also significantly increased. This was attributed to Zn 2+ preventing the degradation of KGM induced by microbial growth. Bacillus and Paenibacillus were "culprits" in the viscosity reduction of KGM hydrosol. Zn 2+ maintained the long-term viscosity stability of the hydrosol by inhibiting microbial growth and enzyme activity of β-mannanase. Zinc sulfate, zinc acetate, and zinc gluconate being edible salts were also used as a source of zinc ions and showed a similar long-term stabilization effect on the viscosity of the KGM hydrosol. These provided a realistic strategy to replace non-edible additives with edible zinc salts for food industry applications. Graphical abstract: Image 1 Highlights: The viscosity of KGM hydrosol dropped sharply after a period of approximately 12 h. Effect of different divalent metal ions on the viscosity stability of KGM hydrosol was investigated. Degradation of KGM led to a sharp reduction in the viscosity of KGM hydrosol. The degradation of KGM was caused by Bacillus and Paenibacillus . Zinc ion inhibited the growth of bacteria and the enzyme activity of β-mannanase.